Ecological factors affecting the spread of class Chilopoda of the group Myriapoda - Hajdar Kicaj (Наукові горизонти, 2023)
Recently, the problem of preserving biodiversity on the planet has become increasingly relevant. Therefore, research on the ecological characteristics of organisms that play an important role in the functioning of biogeocoenoses is especially relevant. Chilipoda millipedes are one of these groups. Currently, many questions on the ecology of Chilopods, especially in the territory of Albania, remain unresolved. This motivates researchers to seek answers to these issues. The primary research aim is to analyse the specific features of the ecology of the Chilipoda millipedes inhabiting Vlora. The material used for the study was the author's collections of centipedes. Manual collection and soil sampling methods were used in the research. Determination of the taxonomic affiliation of centipedes was performed by examining the morphological features of centipedes under a stereoscopic microscope and further determining specimens with the help of determination keys. In the field under investigation, the Chilipoda fauna is represented by 6 species from 4 orders, 6 genera, and 5 families. Temperature and humidity have been shown to have a significant influence on the geographical distribution of chilopods: thus, the occurrence of centipedes in litter and the upper soil layer decreases significantly with the onset of drought. The character of flora plays a secondary role in the distribution of centipedes. It was established that soils with high content of humus and nitrogen are a favourable habitat for centipedes. The paper presents, for the first time for the Vlora region, data on the vertical distribution of S. coleoptrata along the soil profile. Scootigers preferred litter and did not migrate into the soil. Other representatives of Chilipoda were mainly found in the uppermost soil layer (0-10 cm), moreover Chilipoda were concentrated in the litter, and only a small part of them descended to a depth of 20 cm. The obtained results contribute to the knowledge of the ecological features of chilopods